Physical Capacity Survey of Sports Education Student Class 2022 STKIP PGRI Bangkalan - Bahri, Mohammad Syaiful; Hidayatullah, Fajar; Purwoto, Septyaningrum Putri; Widodo, Haryo Mukti (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2024)
Physical strength that uses, endurance and flexibility is physical fitness. Physical fitness factors include (speed, agility, flexibility, endurance, strength, balance). The researcher aims to determine the physical condition of students of the sports education study program class of 2022 at the STKIP PGRI Bangkalan campus. This research uses survey research methods. The sample selection was carried out using purposive sampling. The sample obtained was 35 students from a sample of 28 male students and 7 female students. This research was carried out at the STKIP PGRI Bangkalan campus which was carried out in this study including the Sit & Reach to monitor lower back flexibility, Standing Stork Test to maintain a state of balance, Pess-up Test to assess upper body endurance, Illinois Agility Run Test to monitor speed and agility, Standing Long Jump Test to monitor leg strength. The results show that male and female students have lower back flexibility in the excellent category. Male and female students are balanced in the poor category. Male upper body endurance is average in the below average category and female is in the average category. Male speed and agility with average category and female speed and agility average category. Male leg strength with poor category and female with poor category. The conclusion of this research is that for physical capacity flexibility needs to be maintained, while balance, endurance, speed and agility, strength need to be improved.